Drawing cancer chronicles: A qualitative study to evaluate narrative meaning-making over time and in response to a meaning-centred care intervention - Emily R.E. Evans; Niels van Poecke; Maite Portela; Michael Scherer-Rath; Yvonne Weeseman; Zarah M. Bood; Nirav Christophe; Henny Dörr; Judith de Vos-Geelen; Aart Beeker; Gerty de Klerk; Eric Bras; et al. (PLoS ONE, 2026)
The diagnosis of incurable cancer can disrupt life stories, undermining meaning-making and challenging self-identity. People may therefore need to search for and create new stories about their lives that incorporate their diagnosis. Arts-based narrative interventions are being explored to support this existential process of narrative meaning-making. However, developing effective existential support may be limited by the lack of methods capable of investigating their impact. This study is the first to explore narrative meaning-making across time and a meaning-centred care intervention by longitudinally using ‘Rich Pictures’ (RPs) – hand-drawn visual narratives. We analysed repeated RPs about living with incurable cancer from thirty-eight participants in two studies: one incorporating an arts-based narrative intervention, and one without. RPs were compared across time and the two groups using an inductive, multi-level, and participatory analysis approach. Our findings highlighted six strategies variably used by participants to reconstruct their narratives over time: repeating, retaining, repurposing, reinforcing, reducing, and reassembling. Differences were found in the employment of these strategies between the two different studies, with arts-based intervention participants predominantly developing new ways of narrating and relating to cancer as a disruptive life event. We conclude that people living with incurable cancer employ a range of strategies in reconstructing their narratives. Arts-based interventions may support this existential process. The repeated use of RPs is a valuable method for investigating narrative meaning-making over time, across groups, and interventions, offering insights to evaluate and develop meaning-centred care in oncology.